Investigating Pb Nanostructures with a Density-Functional Tight-Binding Approach: Slater-Koster Parameters - Unigarro, Andres; Günther, Florian [UNESP]; Gemming, Sibylle (American Chemical Society (ACS), 2025)
Intercalation in epigraphene systems is an established technique widely used to modify the electronic structure of graphene and to synthesize otherwise unstable two-dimensional layers with exotic electronic properties. However, capturing the full symmetry of the heterostructure requires a large number of atoms, rendering traditional electronic-structure approaches computationally demanding. Density-functional-based tight-binding (DFTB) offers an efficient alternative, balancing accuracy and reduced computational cost. For heavy elements such as Pb, however, proper parameters for these types of calculations are not available in the open literature. In this work, we developed a Slater-Koster parameter set for the elements Si, C, and Pb, enabling the investigation of the electronic structure of various elemental and binary solid-state structures, such as graphene, plumbene, and silicon carbide. Our results obtained with DFTB for bulk Pb and Pb/SiC structures show good qualitative agreement with pure DFT calculations. Furthermore, the inclusion of spin-orbit coupling (SOC) significantly modifies their electronic properties, aligning with DFT findings. These results underscore the capability of the optimized parameters to accurately model complex systems, allowing investigations of larger systems closer to experimental observations.